2020
DOI: 10.1039/d0ra02874f
|View full text |Cite
|
Sign up to set email alerts
|

Novel TiO2/GO/CuFe2O4 nanocomposite: a magnetic, reusable and visible-light-driven photocatalyst for efficient photocatalytic removal of chlorinated pesticides from wastewater

Abstract: A TiO2/GO/CuFe2O4 heterostructure photocatalyst is fabricated by a simple and low cost ball milling pathway for enhancing the photocatalytic degradation of chlorinated pesticides under UV light irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…Briefly, the increased adsorption capacity of GO‐based NCs (CFT‐GO %3–10% and CF ‐GO) in this study (see BET surface analysis results section above, and Fig. S4) are hypothesized to have caused limited adsorption and decomposition of H 2 O, hindering the formation of OH ∙ and O 2 ∙ species, which are reported to be the dominant oxidative species in the photocatalytic degradation mechanism of MB 68,72,73 …”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…Briefly, the increased adsorption capacity of GO‐based NCs (CFT‐GO %3–10% and CF ‐GO) in this study (see BET surface analysis results section above, and Fig. S4) are hypothesized to have caused limited adsorption and decomposition of H 2 O, hindering the formation of OH ∙ and O 2 ∙ species, which are reported to be the dominant oxidative species in the photocatalytic degradation mechanism of MB 68,72,73 …”
Section: Resultsmentioning
confidence: 84%
“…CFT‐GO may resctrict hole−electron recombination by trapping delocalized electrons. Briefly, the transfer of phot‐generated electron from CF spinel ferrite to Ti nanoparticles through the heterojunction and/or GO layer result gives rise to formation of ROS in the form OH ∙ and O 2 ∙ 68 . The PL exciton peak around 378 cm −1 is ascribed to the recombination of electron and hole.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, it should be reminded that our catalysts did not display photocatalytic activities in the experimental conditions (using a 9 W Osram Dulux S lamp as visible light source and a 9 W Radium 78 lamp as UVA light source) although in some studies, the authors reported the photocatalytic activity of CuFe 2 O 4 materials. For these studies, the authors usually used a 500 W xenon lamp [Zhu et al 2013] or a 150 W xenon arc lamp [Ismael et al 2020]. Their capacity is much higher than that of our lamps (only 9 W).…”
Section: Discussionmentioning
confidence: 99%